Natural history of COVID-19 recovery: Changes in physiologic, radiologic and patient-reported outcomes 12 months after symptom onset. Issue 4 (28th July 2022) - Wong, Alyson W.; Shah, Aditi S.; Hague, Cameron J.; Johnston, James C.; Ryerson, Christopher J.; Carlsten, Christopher
Abstract: RATIONALE: The long-term trajectory of people recovering from COVID-19 and the cause of persistent symptoms remains poorly understood. OBJECTIVE: We sought to determine how pulmonary function tests (PFTs), patient-reported outcome measures (PROMs) and radiologic features change over 12 months in people hospitalized with COVID-19. METHODS: A prospective, consecutive cohort of patients hospitalized with PCR-confirmed SARS-CoV-2 were recruited. Longitudinal clinical data, PROMs, PFTs and computed tomography (CT) chests were collected at 3, 6 and/or 12 months after symptom onset. Repeated analysis of variance (ANOVA) and Friedman tests were used to compare changes in outcomes over time. MEASUREMENT AND MAIN RESULTS: Eighty-one patients were enrolled with 70 completing the 12-month visit. At 3 months, the mean diffusing capacity of the lung for carbon monoxide was reduced at 76 ± 16%-predicted and improved to 80 ± 16%-predicted at 6 months (p < 0.001). The median values for dyspnea, cough, sleep and quality of life (QoL) were abnormal at 3 months, with QoL being the only PROM that significantly improved at 6 months. There was no further statistically significant change in PFT parameters or PROMs between 6 and 12 months. The percentages of lung affected by ground glass and reticulation at 3 months were 11.3% (IQR 5.6–19.6) and 4.4% (IQR 1.6–7.9), respectively. These improved at 12 months with ground glass being 0% (IQR 0-3.3) and reticulation 1.7% (IQR 0–3.3). CONCLUSIONS: PFTs improve between 3 and 6 months, with no change over the subsequent 6 months in patients hospitalized with COVID-19. Despite improved and nearly normal physiologic and radiologic results in most patients, 60% report abnormal PROMs at 12 months.